1972
DOI: 10.1017/s0043174500036146
|View full text |Cite
|
Sign up to set email alerts
|

Light Period, Temperature, and Kochia Flowering

Abstract: Floral induction in kochia(Kochia scoparia(L.) Schrad.) was influenced more by light period and temperature than by soil fertility or soil moisture. Floral induction occurred when the light period per 24-hr cycle was shorter than a critical length. However, the critical duration of light per 24-hr cycle at which floral induction occurred varied from about 13 to 15 hr among kochia selections. The time from emergence to flowering varied from 57 to 100 days. The kochia selection from New Mexico required a shorter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

1974
1974
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…This prevented gene flow from R to S plants during the early flowering stage. However, kochia plants flower indeterminately, and S plants produced new flow- (2). The R biotype had a strong decreasing day-length requirement for flower initiation in the greenhouse, while the S biotype was less sensitive to day length (25).…”
Section: Resultsmentioning
confidence: 98%
“…This prevented gene flow from R to S plants during the early flowering stage. However, kochia plants flower indeterminately, and S plants produced new flow- (2). The R biotype had a strong decreasing day-length requirement for flower initiation in the greenhouse, while the S biotype was less sensitive to day length (25).…”
Section: Resultsmentioning
confidence: 98%
“…The slight delay in seed production at Huntley compared with Havre and Fort Benton is probably within the normal variation of flowering time for kochia. The kochia accessions studied by Bell et al (1972) showed substantial variability in the critical periods required for flowering: of two accessions from Groton, SD, one achieved 50% flowering under a 15 h 2 min daylength whereas the other required a 14 h 11 min daylength.…”
Section: Resultsmentioning
confidence: 99%
“…Kochia is a short day plant that initiates flowering when daylength falls below a critical period (Eberlein and Fore 1984). Bell et al (1972) determined the daylength at which several kochia accessions from northern latitudes of the United States (43ЊN to 48ЊN) achieved 50% flowering when planted at Fargo, ND (46Њ53ЈN). Critical periods required for flowering ranged from 13 h 12 min to 15 h 20 min, with most accessions flowering under 14.5-to 15-h daylength.…”
Section: Introductionmentioning
confidence: 99%
“…Kochia is a problem in late-harvested crops such as soybean, but has adapted to flower and produce seeds in early-harvested crops, such as small grains (Bell et al 1972). Kochia densities may exceed 2,100 seedlings/m 2 and reduce wheat yield more than 20% and soybean yield more than 30%.…”
Section: Introductionmentioning
confidence: 99%